Synthesis of oxadiazole-coupled-thiadiazole derivatives as a potent β-glucuronidase inhibitors and their molecular docking study. Issue 14 (15th July 2019) - Taha, Muhammad; Imran, Syahrul; Alomari, Munther; Rahim, Fazal; Wadood, Abdul; Mosaddik, Ashik; Uddin, Nizam; Gollapalli, Mohammed; Alqahtani, Mohammed A.; Bamarouf, Yasser A.
Graphical abstract: Abstract: A new series of oxadiazole with thiadiazole moiety (6 –27) were synthesized, characterized by different spectroscopic techniques and evaluated for β -glucuronidase inhibitory potential. Sixteen analogs such as 6, 7, 8, 9, 10, 12, 13, 14, 17, 18, 20, 23, 24, 25, 26 and 27 showed IC50 values in the range of 0.96 ± 0.01 to 46.46 ± 1.10 μM, and hence were found to have excellent inhibitory potential in comparison to standard d -saccharic acid 1, 4-lactone (IC50  = 48.4 ± 1.25 μM). Two analogs such as 16 and 19 showed moderate inhibitory potential while analogs 11, 15, 21 and 22 were found inactive. Our study identifies new series of potent β -glucuronidase inhibitors for further investigation. Structure activity relationships were established for all compounds which showed that the activity is varied due to different substituents on benzene ring. The interaction of the compounds with enzyme active site were confirmed with the help of docking studies, which reveals that the electron withdrawing group and hydroxy group make the molecules more favorable for enzyme inhibition.